Recent developments on the optical properties of thin films of chalcogenide glasses. (December 2016) - Sharma, Pankaj; Sharma, Neha; Sharda, Sunanda; Katyal, S.C.; Sharma, Vineet
Abstract: Chalcogenide glasses (ChG) has emerged as important materials due to their potential applications in infrared optics for communication, imaging, limiting, remote sensing and laser power delivery etc . Examining ChG for their various applications, different properties of these were under immense investigation by various researchers from nearly every part of the world. Study of ChG for optical properties like optical band gap and refractive index are the backbone while considering them for applications. The present review focuses on the optical properties of various binary, ternary and quaternary chalcogenide systems. Subsequently applications and future prospects of ChG have been sketched. The attracting prospective applications have drive us to put the review on optical properties of chalcogenide thin films both comprehensive and expedient to new as well as established researchers in this area.